Educational intervention for parents of adolescents with chronic illness: A pre-post test pilot study - Akre, C.; Ramelet, Anne-Sylvie; Berchtold, A.; Suris, J. (Walter de Gruyter GmbH, 2015)
Objective: This pilot experimental study tested the feasibility and intended effect of an educational intervention for parents to help them assist their adolescent child with chronic illness (CI) in becoming autonomous. Methods: A two-phase pre-post pilot intervention study targeting parents of adolescents with CI was conducted. Parents were allocated to group 1 and 2 and received the four-module intervention consecutively. Intended effect was measured through online questionnaires for parents and adolescents before, at 2 months after, and at 4-6 months after the intervention. Feasibility was assessed through an evaluation questionnaire for parents. Results: The most useful considered modules concerned the future of the adolescent and parents and social life. The most valued aspect was to exchange with other parents going through similar problems and receiving a new outlook on their relationship with their child. For parents, improvement trends appeared for shared management, parent protection, and self-efficacy, and worsening trends appeared for coping skills, parental perception of child vulnerability, and parental stress. For adolescents, improvement trends appeared for self-efficacy and parental bonding and worsening trends appeared for shared management and coping skills. Conclusion: Parents could benefit from peer-to-peer support and education as they support the needed autonomy development of their child. Future studies should test an online platform for parents to find peer support at all times and places.